ANALISIS FERTILITAS, KELUARGA BERENCANA DAN PENDIDIKAN PEREMPUAN DI SUMATERA BARAT - Muhammad Alghifari; Ariusni Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to identify and analyze the causality of relationship between fertility, family planning and women's education. This type of research is associative descriptive research, where the data used are secondary data from 2012 to 2016 that use data Vector Error Correction Model (VECM) to see the long and short term at the same time. The findings of this study indicate that fertility and family planning do not have a reciprocal relationship or direction and fertility and women's education has no causality of relationship but has a direct relationship with women's education on fertility and family planning and education women do not have a causality of relationship but have a relationship with 10% confidence level for women's education on family planning.